Giant sialolith at sublingual salivary gland. Biggest? - Abul Fauzi; Irfan Rasul (Journal of Dentomaxillofacial Science, 2018)
Objective: Sialoliths or salivary gland duct calculus are the most common pathologies of the salivary gland. The majority of sialoliths occur in the submandibular gland or its duct and are a common cause of acute and chronic infections. Sialoliths are deposits obstructing the ducts of major or minor salivary glands.Methods: Clinical and radiographic examination panoramic and CBCT was conducted and the diagnosis is sialolithiasis on salivary ducts sublingual gland sinistra and removal of salivary glands stone (sialolithotomy) was planned intraorally with sialodochoplasty under general anesthesiaResults: CBCT and intra operation obtained the stone in the wharton’s duct with 26.5 mm in length and 17 mm in diameter.Conclusion: The main complaint of sialolithiasis is pain accompanied by swelling. The therapy that can be done for this sialolith is divided into conventional techniques without surgery, surgical therapy and therapy with ECSWL techniques.